Association between dietary folate intake and severe headache or migraine in adults: a cross-sectional study of the National Health and Nutrition Examination Survey - Zhao, Dehua; Long, Xiaoqing; Wang, Jisheng (Frontiers in Nutrition, 2024)
The aim of this study was to assess the association between dietary folate intake and severe headache or migraine.Examination Survey (NHANES) data from 1999 to 2004. Weighted logistic regression models, restricted cubic spline (RCS) regression, sensitivity analysis, and stratified analyses were performed to evaluate the association between dietary folate intake and severe headache or migraine.Results: A total of 4107 participants were included, with 704 individuals (17.14%) experienced severe headache or migraine. After adjusting for all covariates, an independent association was found between dietary folate intake and severe headache or migraine (OR=0.77, 95% CI: 0.64-0.93, P=0.005). When folate intake was categorized, individuals in Q2 (251.21-356.00 μg/d), Q3 (356.19-514.00 μg/d), and Q4 (≥515.00 μg/d) had ORs of 0.95 (95% CI: 0.75-1.20, P=0.660), 0.86 (95% CI: 0.67-1.12, P=0.266), and 0.65 (95% CI: 0.48-0.89, P=0.007), respectively, compared to those in Q1 (≤251.00 μg/d). The RCS regression showed a linear negative relationship between dietary folate intake and severe headache or migraine. Stratified and sensitivity analyses yielded similar results.There was a linear negative relationship between dietary folate intake and migraine.